Characterization of Lactic Acid Bacteria (LAB) Isolated from Homemade Fermented Kimchi in Bangladesh (Bangladesh Pharmaceutical Journal, 2024)
The purpose of this present study was to explore lactic acid bacteria (LAB) from homemade kimchi. Traditionally, kimchi was made in this study at home using fresh vegetables such as cabbage, carrots, radish, green onion leaf, red pepper, garlic, ginger, salt and rice flour, and fermented for seven days. LAB were isolated using selective media and identified by macroscopic and microscopic morphological analysis and short biochemical tests such as catalase, oxidase and Kliger's iron agar (KIA) test. Probiotic potential of LAB was investigated by acid, salt, temperature tolerance and sugar including glucose, fructose, sucrose, xylose and lactose fermentation test. Four distinct single colonies were isolated from four different kimchi preparations. All isolated bacteria were identified as lactic acid bacteria and found gram positive, non-spore forming, survive in both aerobic and anaerobic condition, catalase and oxidase negative. Isolated LAB survive in both highly acidic (pH 2) and alkaline (pH 8) medium, up to 4% NaCl concentrations and at temperatures ranging from 4°C to 55°C. The isolated LAB have also ability to ferment sugars. These findings reveal that isolated LAB found suitable to survive in the environment of human gastrointestinal tract and have probiotic potential.Bangladesh Pharmaceutical Journal 27(1): 103-109, 2024 (January)